Hematologic Predictors of Chemotherapy-Induced Neutropenia in Breast Cancer Patients Receiving Anthracycline- or Taxane-Based Chemotherapy - Muhammad Reza Fahlevi (HM Publisher, 2025)
Background: Chemotherapy-induced neutropenia (CIN) is a common and serious complication of chemotherapy in breast cancer patients, leading to increased morbidity, mortality, and treatment disruptions. This study aimed to investigate the association between hematologic profiles and the occurrence of CIN in breast cancer patients receiving anthracycline-based or taxane-based chemotherapy. Methods: A retrospective observational analytic study with a cross-sectional design was conducted using medical records of breast cancer patients treated at the Oncology Surgery Clinic between 2022 and 2023. Sixty patients were included in the study. Hematologic profiles, including hemoglobin and leukocyte counts, were analyzed to assess their association with CIN in both anthracycline- and taxane-based chemotherapy groups. Results: The majority of patients were aged 15-64 years (86.67%), normoweight (65%), had luminal B subtype (63.3%), and were in the locally advanced breast cancer (LABC) stage (45%). Most patients were non-anemic (Hb ≥12 mg/dL) and leukopenic (71.7% and 80%, respectively). No significant association was found between age, nutritional status, or breast cancer stage and CIN (p > 0.05). However, hemoglobin and leukocyte profiles were significantly associated with CIN in both chemotherapy groups (p < 0.05). No association was found between the type of chemotherapy (anthracycline- or taxane-based) and CIN occurrence. Conclusion: Anemia (Hb <12 g/dL) and leukopenia are significant predictors of CIN in breast cancer patients, regardless of the chemotherapy regimen. These findings highlight the importance of monitoring hematologic profiles in these patients to identify those at higher risk of CIN and implement appropriate preventive and management strategies.